Lymph Node Invasion by Melanoma Cells Is Not Required for the Induction of Incomplete Differentiation by Tumor‐Specific CD8+ T Cells - Kristian M. Hargadon; Travis B. Goodloe III; Stephen L. Woodall II (Cancer Reports)
ABSTRACT Background Lymph node invasion by cancer cells is a poor prognostic factor and is often associated with anti‐tumor CD8+ T cell dysfunction. In this study, we investigated the role of lymph node invasion by melanoma cells in the induction of incomplete differentiation by tumor antigen‐specific CD8+ T cells. Aims We aimed to determine whether lymph node invasion by melanoma cells is required for this specific form of anti‐tumor CD8+ T cell dysfunction. Methods and Results We assessed lymph node invasion by the B16‐F1 and D5.1G4 murine melanoma cell lines and evaluated tumor antigen‐specific CD8+ T cell responses to these melanomas in the context of tumor‐free versus tumor‐involved lymph nodes. We demonstrate that CD8+ T cells recognizing antigen from established melanomas fail to acquire effector function, regardless of whether the tumor is stable or progressive. This CD8+ T cell dysfunction arises in the context of both tumor‐involved and tumor‐free lymph nodes draining established melanomas. Conclusions Lymph node invasion by melanoma cells is not required for the induction of incomplete CD8+ T cell differentiation. These data and their implications for strategies to enhance CD8+ T cell responses against poorly immunogenic melanomas are discussed herein.